A retrospective study of outcome for patients referred for oesophageal studies from a district general hospital respiratory clinic. (13th March 2011) - Ebert, B; Noble, K; Vathenen, S; Brocklebank, D; Abusriwil, H; Aldulaimi, D
Abstract : Introduction: Oesophageal manometry and pH studies can be used to evaluate patients with atypical reflux symptoms, such as chronic cough, or recurrent chest infections, bronchiectasis and pulmonary fibrosis. Patients with demonstrated reflux that fail to respond to PPI therapy may be considered for antireflux surgery. Few studies have reported outcomes for patients referred for oesophageal studies from respiratory clinics based in district general hospitals. Methods: We retrospectively identified and reviewed the records of all patients referred from a general respiratory clinic for oesophageal manometry and pH studies. Results: 112 patients were referred for oesophageal pH studies from respiratory clinic. The most common presenting symptom was cough (63 patients), other indications included recurrent chest infections (26), bronchiectasis (23) and pulmonary fibrosis (9). 110 patients tolerated the procedure; 74 patients (67.3%) were found to have significant acid reflux. 33 patients were referred for surgical opinion. Reasons not to refer included patient refusal, poor lung function, obesity and resolution of symptoms. 25 patients had antireflux surgery. 30% of patients reported an improvement or resolution of symptoms post surgery. Conclusion: Oesophageal studies and antireflux surgery are of benefit to a significant proportion of carefully selected patients from routine respiratory clinics.